Differential impacts of COVID-19 lockdown on informal workers in Goa: A gendered and sectoral analysis - Manerkar, Gouri Kanta; Chandran, B P Sarath (Journal of Social Economics Research, 2025)
The COVID-19 pandemic severely impacted informal workers in terms of employment and income, especially in tourism-dependent economies such as Goa in India. The paper examined the socioeconomic vulnerabilities experienced by informal workers during the COVID-19 pandemic, with particular attention to gender, employment sector, and migrant status. Using a mixed methods approach, the study collected data from 250 informal workers employed in Goa’s formal and informal sectors to examine employment vulnerability. Findings from the binary logistic model indicated that a significant proportion of informal workers lost their jobs during the lockdown, with women, migrants, and daily wage earners facing the highest risks. Informal workers employed in the informal sectors are more susceptible to job loss, and their chances of reemployment are lower compared to their counterparts in the formal sectors. Due to multiple job roles and caregiving responsibilities for their families, women are more likely to experience job loss and less likely to regain employment after the pandemic. The lack of social security and challenges related to reverse migration increase the vulnerability of migrant workers during the pandemic. Education serves as a protective buffer, as higher levels of education decrease the likelihood of job loss. The paper strongly advocates for urgent, targeted policy interventions, including expanded social security, sector-specific relief programs, and alternative livelihood options to enhance resilience in tourism-dependent informal economies. The findings contribute to a better understanding of the labor market disruptions caused by the pandemic and highlight the importance of developing inclusive recovery strategies.